RHETORIC IN RELIGIOUS TEXTS - Turakhanova Badia (Galaxy International Interdisciplinary Research Journal, 2024)
This article delves into the intricate world of religious texts, unveiling the rhetorical nuances embedded within their sacred verses. Through a meticulous analysis of diverse rhetorical devices employed across various religious traditions, the study explores the historical, cultural, and theological dimensions of these texts. By comparing and contrasting the rhetoric in different religious scriptures, the research sheds light on how rhetorical choices shape interpretations of religious doctrines. Ultimately, this investigation contributes to a deeper understanding of the persuasive and emotive elements within religious texts, offering insights into their profound impact on belief systems and cultural practices.